Border as method - Jurić-Pahor, Marija (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The first wave of the Covid-19 pandemic demonstrated that the "border as method" (Mezzarda & Neilson) is paradigmatically established and proliferates in the borderland of a nation-state. Analysing the prevailing political, media and public discourse and focusing on the border area between Italy and Slovenia, the article illustrates that borders are not located only on the edges of a territory, but also extend inside and outside such. They are part of broader social processes of border internalisation in the management of population movements. During the pandemic, the tendency to strengthen control of the Schengen border and of the border between Italy and Slovenia gained new impetus. The border was invoked in relation to the risk of infection, thus implying adiaphorisation and exclusion ("We are not Italy!"), and also as the locus that - particularly among the Slovene minority and the people living along the border - raised awareness about the need for empathic, cross-border and European integration in the sense of transcending national borders.
Keywords: Italija; mejno območje; nezakonite migracije; pandemija covid 19; Slovenija; slovenska manjšina; slovensko-italijansko obmejno območje